DEVELOPING L2 READING SKILLS USING THINKING ALOUD STRATEGIES - Paramjit Kaur; Aizan Yaacob; Qistina Marzuki (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This study examined the use of the think-aloud strategy to enhance reading skills among students in a public university in Malaysia. Ten participants were involved in this study. All the participants were required to use the think-aloud strategy while reading two pre-determined texts. Data collection included semi-structured interviews with all the participants and the participants’ think-aloud protocols that were audio-recorded. These recordings and interviews were transcribed and analysed for themes. The findings from the think-aloud sessions showed that the strategy encouraged participants to engage critically and actively with the texts, which in turn allowed them to understand the underlying messages of the texts. Data from the interviews also suggested that participants found that the think-aloud strategy increased their metacognitive abilities in reading. Participants expressed that the think-aloud strategy in general helped them improve their reading and comprehension skills. The think-aloud strategy can be used in second language (L2) reading classes to develop metacognitive abilities as well as develop critical reading skills. Students and teachers can be trained to use the think-aloud strategy as an activity to enhance their reading skills.